PENGARUH LATIHAN OPERAN DAN PENERIMAAN INSIDE-OF-THE-FOOT TERHADAP KETERAMPILAN PASSING DAN STOPPING PADA EKSTRAKURIKULER SMP NEGERI 3 ROKAN IV KOTO KABUPATEN ROKAN HULU - Ardiansyah, Hendrik; ', Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem with this research it still a lack of skil passing and stopping at the time of the snap on SMP NEGERI 3 Rokan IV Koto Kabupaten Rokan Hulu.Based on the researchers training provide pass and acceptance inside-of-the-foot. The research to determine whether there is effect pass and acceptance inside-of-the-foot exercises to the skill of passing and stopping extracurricular of SMP NEGERI 3 Rokan IV Koto Kabupaten Rokan Hulu, so that when a pass and acceptanceof the ball get the passing and stopping maximum lea. The research is experimental treatment (Experimental), with a population extracurricular of SMP NEGERI 3 Rokan IV Koto Kabupaten Rokan Hulu, the data in this research is the entire population of 16 people. The instruments used in this research is to test Johnson soccer tes, which aims to measure the general ability in football. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the effect pass and aceptance inside-of-the-foot exercises to the skill of passing and stopping. Based on the analysis of statistical data, there are an average Pree-test of 10,12 and an average post-test 12,18, then the data is normal with an increase of 2,06. Based on t test analysis produces Ttabel Thitung of 5,42 and 1,753, meaning Thitung> Ttabel. Thus, there Effect of Exercise pas and acceptance inside-of-the-foot on the skill of passing and stopping extracurricular of SMP NEGERI 3 Rokan IV Koto Kabupaten Rokan Hulu.Keywords : Pass And Acceptance Inside-Of-The-Foot, The Skill Passing And Stopping.